Notes on the genus Grouvellinus Champion, 1923 (Coleoptera: Elmidae) from Xizang Autonomous Region, China, with description of a new species - Jiang, Ri-Xin; Chen, Xiang-Sheng (Zootaxa, 2026)
The genus Grouvellinus Champion, 1923 comprises 67 described species distributed across the Oriental and Palearctic regions. Species diversity of this genus is very high in mainland China, with 33 recorded species, and three of these were recorded from Xizang Autonomous Region, China. In the present paper, we describe a new Grouvellinus species from Mêdog County, a distribution map and a list of all species of Grouvellinus known from Xizang Autonomous Region are provided.